Congruency of multimodal data-driven personalization with shared decision-making for StayFine: individualized app-based relapse prevention for anxiety and depression in young people - Kooiman, Bas E. A. M.; Robberegt, Suzanne J.; Albers, Casper J.; Bockting, Claudi L. H.; Stikkelbroek, Yvonne A. J.; Nauta, Maaike H. (Frontiers in Psychiatry, 2023)
Tailoring interventions to the individual has been hypothesized to improve treatment efficacy. Personalization to target specific underlying mechanisms might improve treatment effects as well as adherence. Data-driven personalization of treatment, however, is still in its infancy, especially concerning the integration of multiple sources of data-driven advice with shared decision-making. This paper describes an innovative type of data-driven personalization in the context of StayFine, a guided app-based relapse prevention intervention for 13-to-21-year-olds in remission of anxiety or depressive disorders (n = 74). Participants receive six modules, amongst which 3 are chosen from 5 optional modules. Optional module are Enhancing Positive Affect, Behavioral Activation, Exposure, Sleep and Wellness. All participants receive Psycho-Education, Cognitive Restructuring, and a Relapse Prevention Plan. The personalization approach is based on 4 sources: (1) prior diagnoses (diagnostic interview), (2) transdiagnostic psychological factors (online self-report questionnaires), (3) individual symptom networks (ecological momentary assessment, based on a two-week diary with six time points per day) and subsequently (4) patient preference based on shared decisionmaking with a trained expert by experience. This paper details and evaluates this innovative type of personalization approach, comparing the congruency of advised modules between the data-driven sources (1-3) with one another and with the chosen modules during the shared decision-making process (4). Results show that sources of data-driven personalization give complementary rather than confirmatory advice. Indication of the modules Exposure and Behavioral Activation were mostly based on the diagnostic interview, Sleep on the questionnaires, and Enhancing Positive Affect on the network model. Shared decision-making showed preference for modules improving positive concepts rather than combating negative ones, as an addition to the data-driven advice. Future studies need to test whether treatment outcomes and drop-out rates are improved through personalization.